Renal function following xenon anesthesia for partial nephrectomy—An explorative analysis of a randomized controlled study - Stevanovic, Ana (PLoS One, 2017)
BACKGROUND: Perioperative preservation of renal function has a significant impact on morbidity and mortality in kidney surgery. Nephroprotective effects of the anesthetic xenon on ischemia-reperfusion injury were found in several experimental studies. OBJECTIVE: We aimed to explore whether xenon anesthesia can reduce renal damage in humans undergoing partial nephrectomy and to gather pilot data of possible nephroprotection in these patients. DESIGN: A prospective randomized, single-blinded, controlled study. SETTING: Single-center, University Hospital of Aachen, Germany between July 2013-October 2015. PATIENTS: Forty-six patients with regular renal function undergoing partial nephrectomy. INTERVENTIONS: Patients were randomly assigned to receive xenon- (n = 23) or isoflurane (n = 23) anesthesia. MAIN OUTCOME MEASURES: Primary outcome was the maximum postoperative glomerular filtration rate (GFR) decline within seven days after surgery. Secondary outcomes included intraoperative and tumor-related data, assessment of further kidney injury markers, adverse events and optional determination of renal function after 3–6 months. RESULTS: Unexpected radical nephrectomy was performed in 5 patients, thus they were excluded from the per-protocol analysis, but included in the intention-to-treat analysis. The maximum postoperative GFR decline was attenuated by 45% in the xenon-group (10.9 ml min(-1) 1.73 cm(-2) versus 19.7 ml min(-1) 1.73 cm(-2) in the isoflurane group), but without significance (P = 0.084). Occurrence of adverse events was reduced (P = 0.003) in the xenon group. Renal function was similar among the groups after 3–6 months. CONCLUSION: Xenon anesthesia was feasible and safe in patients undergoing partial nephrectomy with regard to postoperative renal function. We found no significant effect on early renal function but less adverse events in the xenon group. Larger randomized controlled studies in more heterogeneous collectives are required, to confirm or refute the possible clinical benefit on renal function by xenon. TRIAL REGISTRATION: ClinicalTrials.gov NCT01839084 and EudraCT 2012-005698-30